Uji Daya Hasil Cabai Rawit (Capsicum annuum L.) Generasi F8 Silangan Varietas Bara x Lokal Sukabumi di Dataran Rendah - Mustafa, Marlina; Syahri, Yolanda Fitria; Ansah, Aldi (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
This study aims to obtain cayenne pepper genotypes that have superior growth characteristics. This research was conducted in Popalia Village, Tanggetada District, Kolaka Regency. This research started from September 2021 to March 2022. This study used nine genotypes of cayenne pepper consisting of six F8 generations, namely: F8145291-115-81-1-1-9(G1), F8145291-4-13- 9-8-1-4(G2), F8145291-14-9-3-12-1-8(G3), F8145291-4-13-9-8-1-6 (G4), F8145291-4-13 -9-8-1-3(G5), F8145291-115-81-1-1-11(G6), which was then compared with three commercial cayenne varieties, namely: Cakra Putih(G7), Dewata F1(G8), Lantern (G9). This research was conducted using a randomized block design (RAK), single-factor treatment with nine cayenne genotypes. Each genotype treatment consisted of three replications with 27 experimental units. Each experimental unit consisted of 20 plants, with ten plants used as samples, so there were a total of 270 sample plants. The observed variables included: plant height, stem diameter, flowering age, fruit length, fruit diameter, fruit number, fruit weight, fruit weight per plant and average harvest age. Based on the yield test on growth characters, it was found that the genotype F8145291-115-81-1-1-9 (G1) had the highest average number of fruits, so it has the potential to be developed in the lowlands.